Teacher’s Methods In Teaching English Vocabularies At Sixth Grade Students Of Sd Muhammadiyah 2 Denpasar - Tita Anggara; I Nyoman Udayana; Novita Mulyana (Lembaga Pengembangan Kinerja Dosen, 2023)
This study entitled Teacher’s Methods in Teaching English Vocabularies at Sixth Grade Students of SD Muhammadiyah 2 Denpasar. It aims to find out the methods used by the English teacher at SD Muhammadiyah 2 Denpasar and the obstacles faced by the teacher. This study used the interview method for collecting data. The data was collected through interviewing the English teacher at the sixth grade students of SD Muhammadiyah 2 Denpasar. In addition, the interview was analyzed according to Richards and Rodgers (1986) in the book of Approaches and Methods of Language Teaching. The result of the analysis shows that the teacher uses the combination between audiolingual method and grammar translation method in teaching vocabularies. There were found several obstacles including the lack of students’ pronunciation and the lack of student’s memorization due to the limited time of study in class.